2015
DOI: 10.5152/akd.2015.6227
|View full text |Cite
|
Sign up to set email alerts
|

Determination of reference values for tricuspid annular plane systolic excursion in healthy Turkish children

Abstract: Objective:Tricuspid annular plane systolic excursion (TAPSE) is an echocardiographic measurement used for evaluating right ventricular systolic function. While established reference values of TAPSE exist for the adult population, only a limited number of studies have attempted to evaluate reference values for the pediatric population. The aim of the present study was to determine the reference values for TAPSE in healthy children in Turkey.Methods:A total of 765 healthy children aged between 0 and 18 years, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
5
16
2
1
Order By: Relevance
“…Decreased annular displacement of the lateral walls of the RV and LVs has been suggested to be an indicator of cardiac dysfunction, which is unaffected by the ventricular preload and correlated with the ejection fraction in studies of children and adults . Previous studies of longitudinal displacement have focused primarily on evaluations of the lateral wall annulus using M‐mode US .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased annular displacement of the lateral walls of the RV and LVs has been suggested to be an indicator of cardiac dysfunction, which is unaffected by the ventricular preload and correlated with the ejection fraction in studies of children and adults . Previous studies of longitudinal displacement have focused primarily on evaluations of the lateral wall annulus using M‐mode US .…”
Section: Discussionmentioning
confidence: 99%
“…Decreased annular displacement of the lateral walls of the RV and LVs has been suggested to be an indicator of cardiac dysfunction, which is unaffected by the ventricular preload and correlated with the ejection fraction in studies of children and adults. 12,[50][51][52][53][54] Previous studies of longitudinal displacement have focused primarily on evaluations of the lateral wall annulus using M-mode US. 26,41,44,45,55 Although this approach provides important information regarding the contribution of the lateral and septal walls to ventricular contractility, it does not globally evaluate basal annular displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of longitudinal APSE has been demonstrated to be an indicator of cardiac dysfunction, unaffected by ventricular preload, and correlated with ejection fraction in studies of children and adults. 12,[24][25][26][27][28] For this reason, examination of the APSE from the right ventricular and left ventricular lateral and septal walls in the fetal heart may be an important tool for evaluation of basal-apical longitudinal contractility. Using the technique described in the current study identifies the endocardium abutting next to the annular insertion of the mitral and tricuspid valve leaflets (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have evaluated the use of TAPSE and MAPSE in adults; however, studies investigating TAPSE and MAPSE during childhood are scarce 3–10 . Children have shorter TAPSE and MAPSE values which are correlated positively both with age and body surface area (BSA).…”
Section: Introductionmentioning
confidence: 99%
“…Children have shorter TAPSE and MAPSE values which are correlated positively both with age and body surface area (BSA). Although TAPSE and MAPSE values are measured routinely in many clinics performing echocardiographic examination, few studies have so far reported their normal values in children 3–10 . In this study, we aimed to define reference ranges for TAPSE and MAPSE in a wide series of healthy children (n = 1300) aged 0‐18 years.…”
Section: Introductionmentioning
confidence: 99%